Ultralight Co/Ag composite foams: Synthesis, morphology and compressive property. (May 2016) - Jiang, Bin; Yang, Xudong; Niu, Weifei; He, Chunnian; Shi, Chunsheng; Zhao, Naiqin
Abstract: Ultralight monolithic Co/Ag composite foams were synthesized by a novel and facile method based on the traditional electroless plating. The resultant foams had remarkably low densities down to 12.7 mg/cm 3 or 99.9% porosity. Morphology of the Co/Ag composite foams was studied and compressive properties of the foam were investigated in light of its relative density. The densification strain of the foam can reach 87% because of the ultralow density. The compressive yield strength was measured and found to be in agreement with the value predicted by the cellular solids theory. Graphical abstract: